Method and system for measuring and calculating cost of power transformation project - LIANG MINXIN; FAN XINTIAN; LIANG YI; HUANG XIAOJIA; LIN ZIHAN; FANG MING; DONG HONG; LI XIN; CHEN WEIZHE; WANG ZHIHUI; HU LONG; CHEN MINGLAN; et al. (2024)
The invention provides a method and system for measuring and calculating the cost of a power transformation project, and the method comprises the steps: obtaining the historical cost data of the power transformation project, and carrying out the preprocessing of the historical cost data, so as to obtain the corresponding preprocessing data; performing factor analysis on the project cost process based on the project information of the typical power transmission and transformation project to construct a cost influence factor library; performing data analysis on the cost influence factor library to optimize and form a corresponding key technical and economic index library; constructing a power transformation project cost prediction model according to the key technical-economic index library, and performing model inspection on the power transformation project cost prediction model based on undetermined parameters of the power transformation project cost prediction model to obtain corresponding prediction errors;